Pengaruh Bahasa Matematika Terhadap Psikologi Siswa Dalam Proses Pembelajaran: Systematic Literature Review - Alvian Bagus Agatha Alvin; Susanto Susanto; Abi Suwito (Universitas Islam Jember, 2026)
This study aims to analyze the influence of mathematical language on students’ psychological conditions in mathematics learning through a Systematic Literature Review (SLR) approach. The review examined articles published between 2015 and 2025 that discussed mathematical language, mathematical communication, and the psychological implications for learners. A total of 10 selected articles were analyzed based on research characteristics, participants, study design, and main findings. The synthesis results indicate that understanding mathematical language has a significant effect on students’ critical thinking skills, problem-solving abilities, and cognitive development. Difficulties in comprehending mathematical symbols, terminology, and structures may trigger anxiety, decreased learning motivation, and mathematics anxiety. Conversely, mastery of mathematical language enhances mathematical communication, academic self-confidence, and emotional intelligence. These findings underscore the importance of employing clear mathematical language, linguistic scaffolding, and adaptive learning strategies to foster positive cognitive and emotional learning experiences. Keywords: mathematical language, students’ psychology